2018
DOI: 10.1007/s10067-018-4151-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary habits on the pathogenesis of rheumatoid arthritis: a case-control study

Abstract: It has not been clear what kinds and how much nutrients could be harmful, preventive, or healthful for development of rheumatoid arthritis. This study aimed to determine the impact of dietary habits on the pathogenesis of rheumatoid arthritis. This case-control study was conducted on a total of 500 rheumatoid arthritis patients and 500 healthy controls refereed to three clinics of Shiraz University of Medical Sciences in 2015-2016. Convenience sampling was used for data collection in both case and control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…It is well known that patients with RA commonly have iron deficiency 43 44. Rambod et al have demonstrated a number of significant differences between the diets of patients with RA and control subjects and it is possible that the significant differences in Cd levels reported here in the patients with RA could represent differences in diets and this would be subject to further research 45…”
Section: Discussionmentioning
confidence: 74%
“…It is well known that patients with RA commonly have iron deficiency 43 44. Rambod et al have demonstrated a number of significant differences between the diets of patients with RA and control subjects and it is possible that the significant differences in Cd levels reported here in the patients with RA could represent differences in diets and this would be subject to further research 45…”
Section: Discussionmentioning
confidence: 74%
“…Finally, there have been multiple studies detailing the effects of green tea consumption in RA patients and reduction in disease activity score-28 (DAS28) as well as better pain management. Moreover, green tea was shown to prevent RA more effectively when compared with high fat beverages [ 122 ].…”
Section: The Use Of Plant Natural Products For Arthritis Therapymentioning
confidence: 99%
“…By grouping the tea consumption into 3 levels, we found that the negative relation between tea and DAS28-ESR happened in a dose-response manner (p for trend < 0.01). A previous study has reported that RA development and intake of green tea are negatively associated [9]. However, this study focused only on the correlation between green tea and RA development, and it did not pay attention to the quantity of tea and the disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, it was found that consuming tea was associated with a reduced risk of mortality, oral cancer and psychological distress [7,8]. More recently, it has been shown that green tea might have preventive effects on the development of RA (OR 0.65, CI 0.45-0.93) [9]. Another small-scale clinical trial showed that RA patients treated with green tea for 6 months alone or in combination with infliximab had significant improvement in disease activity [10].…”
mentioning
confidence: 99%